Mathematical Communication Characteristics of Pre-Service Primary School Teacher in Explaining the Area of Trapezoid Reviewed from School Origin - Zainal Abidin (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2018)
Abstract. This study aims to know the characteristics of mathematical communication of pre-service primary school teachers. The material used as the object of research is geometry. It requires the ability of algebra and spatial skills. The area of trapezoid is selected as the topic since it is perceived as the most complex of all plane shapes studied in primary school. It is because the calculation of the area of trapezoid entails three variables. The ability of mathematical communication involves the ability to write and explain. This ability is examined based on the background of students’ secondary school. The subjects of this study were 15 students of Primary Teacher Education, STKIP Al Hikmah Surabaya in academic year 2017-2018. The types of mathematical communication are grouped according to their characteristics. Written communication is sharpened by oral communication. The results were analyzed to investigate the relevance of such abilities with the subjects’ background of their secondary school (SMA, SMK, or MA). The results indicate that the characteristics of written communication consist of: (1) narrative, (2) procedure, and (3) dialogue. Meanwhile, the characteristics of oral communication consist of: (1) lecture, (2) instructional, and (3) discussion. Pre-service teachers graduated from SMA have better mathematical communication skills than those from SMK and MA. Keywords: Pre-service primary school teacher, mathematical communication, the area of trapezoid.